Maternal hydronephrosis in normal pregnancy in Bayelsa state, South-South Nigeria - Oriji, Peter Chibuzor; Kiridi, Enefia Kelvin; Abasi, Issac Joel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Hydronephrosis is a common finding in normal pregnancy. It is the dilatation of the renal calyces and pelvis by urine, as a result of obstruction of the outflow of urine distal to the renal pelvis. It is usually physiological. The objective of this study was to determine the prevalence of maternal hydronephrosis, and correlate it with age, parity and gestational age in normal pregnancy in Bayelsa State, Nigeria. Methods: This prospective study was conducted at the obstetrics and gynaecology, and radiology departments of the two tertiary hospitals in Bayelsa State, Nigeria, over a six-month period. Sonographic measurements of pelvicalyceal diameters of 400 consecutive normal pregnant women were done, after written informed consent. Data were entered into a pre-designed proforma, and analysed using Statistical Product and Service Solutions (SPSS) version 25.0. Results were presented in frequencies and percentages for categorical variables; mean and standard deviation for continuous variables; Student’s t-test to compare sample means; and Chi-square for associations. Results: Four hundred pregnant women were scanned. Pelvicalyceal dilatation was present in 144 (36%) women; it affected one kidney in 108 (27%) women; while in 36 (9%) women, the two kidneys were affected. Renal calculi were present in 16 (4%) women. The right kidney was affected in 12 (3%) women and the left kidney in 4 (1%) women. Conclusions: The prevalence of hydronephrosis in this study is lower than that from many centres. Pelvicalyceal dilatation was more on the right, and the degree of dilatation increased with increasing gestational age.